Profile of Fetal Echocardiography in a Tertiary Cardiac Centre of Nepal - Sharma, Poonam; Shrestha, Manish; Shrestha, Pragati; Sharma, Diwakar (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To analyze the fetal echocardiographic diagnosis. Methods: A descriptive study of fetal echocardiographic diagnosis at Shahid Gangalal National Heart Centre between October 2016 to September 2017. Results: Total of 615 fetal echocardiography was performed in 607 pregnancies. Intrauterine heart disease noted in 79 cases. Echogenic intracardiac foci was the most common abnormality (6%) followed by VSD (1.3%), fetal arrhythmia (1.1%), pericardial effusion (1.6%), cardiomyopathy (0.3%), hypoplastic left ventricle (0.6%), DORV (0.3%) and tricuspid atresia (0.4%). Similarly the most common referral for fetal echocardiography was for maternal disorder mostly diabetes mellitus. Conclusion: Fetal echocardiography is an important tool for the antenatal diagnosis of congenital heart defects. Appropriate timing and judicious use increases the sensitivity and improves the perinatal outcome of newborns with congenital heart disease